The Formative Years of the Modern Corporation: The Dutch East India Company VOC, 1602–1623 - Gelderblom, Oscar; de Jong, Abe; Jonker, Joost (The Journal of economic history, 2013)
With their legal personhood, permanent capital, transferable shares, separation of ownership and management, and limited liability, the Dutch and English colonial trading companies VOC and EIC are considered institutional breakthroughs. We analyze the VOC's business operations and financial policy and show that its novel corporate form owed less to foresight than to piecemeal engineering to remedy design flaws. The crucial feature of managerial limited liability was not, as previously thought, integral to that design, but emerged only after protracted experiments with various solutions to the company's financial bottlenecks. Legal form followed economic function, not the other way around.